Algorithmic Aspect and Iterative Approximation of a Solution for a System of Generalized Multi-Valued Variational-Like Inclusions in Banach Spaces. (25th January 2023) - Balooee, Javad; Chang, Shih-sen; Liu, Min; Zhu, Jinhua
Abstract: The main purpose of this paper is to construct a new iterative algorithm using the notion of P - η -resolvent operator for solving a new system of generalized multi-valued variational-like inclusions in the setting of Banach spaces. As an application of the constructed algorithm, the strong convergence of the sequences generated by our proposed iterative algorithm to a solution of the system of generalized multi-valued variational-like inclusions is proved.